Comparing Students’ Perceptions in Using Educaplay and Wordwal for Learning Media in Increasing Students’ Engagement - Febrian, Muhammad Fikri; Safriyani, Rizka; Anifaturohmaniah (ICONELT, 2024)
This study compares the effectiveness of Educaplay and Wordwall, two game-based learning platforms, in enhancing student engagement in English learning. A qualitative research design was employed to collect data from 30 middle school students enrolled in English class. The results indicate that Educaplay was more frequently utilized and perceived as more engaging than Wordwall. Students appreciated Educaplay’s interactive features, customizable content, and user-friendly interface, which facilitated a more. These findings highlight the importance of interactivity and personalization in educational tools to improve student engagement, offering insights for educators and developers to create more dynamic and adaptable learning platforms.